HUBUNGAN MENGONSUMSI JAJAN DENGAN STATUS GIZI PADA ANAK SEKOLAH DASAR di SDN 42 PEKANBARU - Rizka Angrainy; Penti Dora Yanti; Desti Yuhelmi (Jurnal Ilmu Kebidanan, 2019)
Eating snacks is one thing that could potentially affect the nutritional status of school children. Nutritional status is more or less nutritional status will affect the value or the learning process at school. Snack foods contributed respectively reach to 22.9% and 15.9% of the total energy and protein intake of elementary school children. A preliminary survey conduct on 10 students, consisting 8 of them admitted that often the snack. This study aims to determine whether there is a relationship eating snacks and nutritional status of school children in SDN 42 Pekanbaru. This research is a quantitative analytic with cross sectional design. The experiment was conducted at SDN 42 Pekanbaru. The population sample of 463 people and 82 people with stratified random sampling technique. Data were obtained from questionnaires, measurement of height and weight directly to the respondent. Statistical analysis using chi-square. The results of the univariate analysis of the majority of respondents answered frequent snacks (63.4%) and consisting of 52 people are consuming unhealthy snacks. The results of chi-square analysis obtained P value <α (0.042 <0.05). which means there is any significant association eat snacks with nutritional status. Parents and the school, is expected to pay more attention to hygiene and nutritional snacks that regular consumption of school children, because what they were used to, will affect the nutritional status of children.